(untitled) (Tempo e Argumento, 2022)
This paper aims to explore some methodological issues discussed in the first article of the series “The imbalance of stories part I” (TÉO, 2018), based on the trajectory of Diva Inclusive Solutions, an initiative founded by the author. The text describes the process of constitution around the problem that gives the title to the two articles, as well as some of the solutions created to fight it, to finally propose possible readings regarding the entry of professionals in the field of humanities in other instances beyond teaching and academic research. Keywords: market; empathy; diversity; technology; unbalance of stories.